Integrating microgenetic algorithms with TLM method for dual-band planar inverted-F antenna design - Chu, H.S.; Dubard, J-L.; Staraj, R. (Electronics letters, 2003)
The efficient coupling between microgenetic algorithms (µGA) and the transmission line matrix method (TLM) to design two planar inverted-F antennas (PIFAs) for dual-band DCS/WLAN and GSM/UMTS standards, respectively, is presented. Measurement results of the µGA/TLM optimised designs show good agreement with numerical simulation for a GSM/UMTS antenna.